2017
DOI: 10.1002/joc.5107
|View full text |Cite
|
Sign up to set email alerts
|

Linking trends in urban extreme rainfall to urban flooding in China

Abstract: Storm‐induced urban flooding is a global issue that causes large damages and fatalities. Characterizing extreme rainfall is critical to urban flood risk management. Although China's cities have been experiencing a rapid increase in urban flooding in recent decades, there is a lack of national‐wide analysis of the occurrence of extreme urban rainfall. This study examined the trends in extreme rainfall in 146 cities in China for the period 1960–2014. The trends were also analysed in terms of city size (small, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…Previous studies have reported that extreme precipitation has changed over the past few decades, but there are apparent discrepancies in regarding these changes over different regions in China, including BTH or North China [73]. Overall, the temporal trends in our work are similar to previous studies in reporting decreasing trends in precipitation extremes over the past few decades in BTH [33,36,40] and the Circum-Bohai-Sea region in the north of China [63,74]. Certainly, there are some discrepancies between our work and previous studies.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous studies have reported that extreme precipitation has changed over the past few decades, but there are apparent discrepancies in regarding these changes over different regions in China, including BTH or North China [73]. Overall, the temporal trends in our work are similar to previous studies in reporting decreasing trends in precipitation extremes over the past few decades in BTH [33,36,40] and the Circum-Bohai-Sea region in the north of China [63,74]. Certainly, there are some discrepancies between our work and previous studies.…”
Section: Discussionsupporting
confidence: 74%
“…As previous mentioned, changes in precipitation extremes are related to the large-scale circulation change [41,42,[77][78][79]. The periodicity characteristics of precipitation extremes will be helpful to understand their associations or linkages with climate indices, which has been investigated in the other regions in previous studies [40,[60][61][62][63][64][65]. Our results showed that the significant two-to five-year periods at the 5% level were predominant for all the indices during the entire period, which are roughly consistent with the previous work of Wang et al [63].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, urban flooding events have frequently occurred in recent years, of which the most catastrophic were the "7.21" flood in Beijing city on 21 July 2012 and the "7.19" flood in Xingtai city of Hebei province on 19 July 2016. The region, therefore, is in a situation with a paradoxical coexistence of increased water scarcity and urban flooding [28]. The paradox in the Jing-Jin-Ji region stimulated many hydrological and hydraulic studies, of which the majority focused on the influences of LULC changes on WY at the individual river basin level for the Hai river, Luan river, Miyun reservoir, Chaobai river, and Baiyangdian river [8,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the urban‐induced effect on precipitation, a second man‐induced effect is global warming, which has contributed to the observed precipitation trend in many regions around the world in the last decades (e.g., Armal et al, ; Parr et al, ; Zhou et al, ). It is a difficult task to distinguish between both global warming and urban‐induced contributions to the observed trend in precipitation, as the sources of observational coverage remain sparse, particularly in the tropics.…”
Section: Decomposition Of Annual Precipitationmentioning
confidence: 99%